Penerapan Metode Eksperimen untuk Meningkatkan Keterampilan Proses Sains Anak Usia Dini: PENERAPAN METODE EKSPERIMEN UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS ANAK USIA DINI - LULUK IFFATUR ROCMAH; NUR HIDAYATUS SHOLIHAH (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2020)
This research is a classroom action research that aims to improve science process skills in early childhood. Science process skills are children's abilities in thinking and investigating the natural environment around a series of learning processes. These skills are abilities that use reason, reason and effective and efficient actions to achieve certain results. With science process skills children can find facts that occur in their environment. Science process skills in group B children in PAUD Tashwirul Afkar are still low, therefore experimental methods are applied in the learning process to improve the condition. The results of applying experimental methods with natural materials can improve the science process skills of group B children in PAUD Tashwirul Afkar. This is indicated by an increase in the percentage of children's science process skills since the action was taken at the pre-cycle, cycle I and cycle II. At the pre-cycle completeness the overall value of the child is 33%. In the first cycle the overall value of the child is 58% and in the second cycle the overall value of the child is 91%.